Core‐shell nanofibers: Integrating the bioactivity of gelatin and the mechanical property of polyvinyl alcohol. Issue 4 (April 2014) - Merkle, Valerie M.; Zeng, Like; Slepian, Marvin J.; Wu, Xiaoyi; Case, David A.
ABSTRACT Coaxial electrospinning is used to fabricate nanofibers with gelatin in the shell and polyvinyl alcohol (PVA) in the core in order to derive mechanical strength from PVA and bioactivity from gelatin. At a 1:1 PVA/gelatin mass ratio, the core‐shell nanofiber scaffolds display a Young's modulus of 168.6 ± 36.5 MPa and a tensile strength of 5.42 ± 1.95 MPa, which are significantly higher than those of the scaffolds composed solely of gelatin or PVA. The Young's modulus and tensile strength of the core‐shell nanofibers are further improved by reducing the PVA/gelatin mass ratio from 1:1 to 1:3. The mechanical analysis of the core‐shell nanofibers suggests that the presence of the gelatin shell may improve the molecular alignment of the PVA core, transforming the semi‐crystalline, plastic PVA into a more crystallized, elastic PVA, and enhancing the mechanical properties of the core. Lastly, the PVA/gelatin core‐shell nanofibers possess cellular viability, proliferation, and adhesion similar to these of the gelatin nanofibers, and show significantly higher proliferation and adhesion than the PVA nanofibers. Taken together, the coaxial electrospinning of nanofibers with a core‐shell structure permits integration of the bioactivity of gelatin and the mechanical strength of PVA in single fibers. © 2013 Wiley Periodicals, Inc. Biopolymers 101: 336–346, 2014.